Library and Information Sciences in Romanian higher education today: Skills and competences - Borş, Silviu (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
After 33 years of existence in Romania, higher education in the field of library and information science is today organized by four universities: the University of Bucharest, Babes Bolyai University of Cluj Napoca, Lucian Blaga University of Sibiu and West University of Timisoara. In 2005, the Bologna Process was also implemented in this field, with specialized education being organized in three specific cycles: undergraduate and master’s studies, postgraduate studies and doctoral studies. Starting with this moment, we are assisting the attempt to standardize the curriculum, implicitly the skills and competencies that graduates must have after graduation. This is supervised by the Romanian Agency for Quality Assurance in Higher Education; the competencies and skills are listed in the register drawn up by the National Agency for Qualifications and correlated with the ESCO register (European Skills, Competences, Qualifications and Occupations). By analysing the latest RAQAHE recommendations (updated in 2022), the ESCO and NAQ registers, we aim to highlight the topicality of the study programmes offered by the four universities. The discussions can be held, in essence, on how well prepared the graduates are for the labour market and what the next steps for a more frequent adaptation of the content of the subjects in the curriculum to take into account the views formulated by The European Network Of Public Employment Services in June 2023, as a contribution to the European Year of Skills. The study also presents the main disciplines included in the curriculum for undergraduate studies recommended by ARACIS and the types of Master’s, postgraduate and doctoral programmes. The main competencies and skills related to the occupations (concerning the information science field) included in the Classification of Occupations in Romania are presented.